Study on the Use of Generative AI in Teaching by Public High School Teachers in Vientiane Capital - SILATTANAKOUN, Sengphet; LOUANGVILAY, Xaythavy; LATTHACHANLA, Bounpheng; KEOPHASOUK, Phaythoon (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research were to: (1) study the basic ICT usage behaviors of high school teachers in Vientiane Capital; (2) examine their satisfaction with the use of Generative AI in teaching and learning; and (3) assess the impacts and concerns related to the use of Generative AI in teaching and learning. This study employed qualitative research methods. The sample consisted of 375 participants, including 188 females, accounting for 50.13% of the total sample. Statistical techniques, including mean (X̄) and standard deviation (S.D.), were used to measure levels of satisfaction and agreement. The findings revealed that, regarding ICT usage behaviors, most teachers use WhatsApp for communication and data transfer, flash drives for transferring large data files, MS Word for document management, and Google Drive for cloud storage. Teachers typically use computers in their daily work for more than 30 minutes at a time, prefer searching for information in the Lao language, favor the Gemini AI program, and regularly use AI in teaching and learning. Regarding satisfaction with the use of Generative AI in teaching and learning, the overall level was found to be good. Specifically, teachers agreed that AI helps reduce time spent on lesson preparation (X̄ = 3.95, S.D. = 0.87), is an effective tool for improving teaching quality (X̄ = 3.81, S.D. = 0.51), assists in content creation and idea generation (X̄ = 4.16, S.D. = 0.71), and motivates them to learn new skills for using AI in teaching (X̄ = 3.78, S.D. = 0.59). In terms of impacts and concerns related to the use of Generative AI in teaching and learning, the overall level was high. Key concerns included excessive reliance and trust in AI (X̄ = 3.73, S.D. = 0.64), the potential reduction of teachers’ creativity (X̄ = 3.40, S.D. = 0.79), and the possibility of widening the gap between teachers in remote rural areas and those in urban areas (X̄ = 3.65, S.D. = 0.80). Overall, the findings indicate that high school teachers in Vientiane Capital are ready to adopt Generative AI in teaching and learning.